Treatment of allergic rhinoconjunctivitis: a review of the role of topical levocabastine - R. Gerth van Wijk (Mediators of Inflammation)
Lcocabastine is an extremely potent and highly selective H1-receptor antagonist which has been specifically developed as eye drops and nasal spray for the treatment of allergic rhinoconjunctivitis. Clinical experience to date suggests that this topical antihistamine is at least as effective as other current first-line therapeutic approaches for the treatment of this condition, including oral H1-receptor antagonists and sodium cromoglycate. Onset of action is rapid, with clinical effects apparent within minutes of instillation. Moreover, duration of action is sufficiently long to permit a convenient twice-daily dosing regimen. Topical levocabastine is well tolerated with an adverse-effect profile comparable with that of placebo and sodium cromoglycate. As might be expected from the route of drug administration, application site reactions are the most frequent adverse effect associated with levocabastine eye drops and nasal spray with an incidence comparable with that seen in placebotreated controls. The availability of effective and well-tolerated topical antihistamines, such as levocabastine, is an important advance which broadens the range of therapeutic approaches available for the clinical management of allergic rhinoconjunctivitis. Levocabastine appears to be an attractive alternative to oral antihistamines as a first-line therapeutic option for the treatment of this atopic condition.